Teknik fotogrametri untuk mendapatkan model studi digital tiga dimensi dalam perawatan ortodonti - Gadih Pratomo, Harris; Arief Budiman, Johan (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
In the field of orthodontics, study models play an important role as diagnostic aids, photogrammetry techniques are used to obtain three-dimensional digital study models. This study model provides an accurate representation of the patient's teeth and occlusion, as well as assists in identifying dental and bone anomalies. In the creation of study models, traditional techniques using cement or gypsum are time-consuming and prone to inaccuracies. Three-dimensional scanning is the process of collecting and analyzing real-world objects or environments using digital data against their possible shapes and appearances. The collected digital data is then processed using three-dimensional scanning software so that it can be used to create three-dimensional digital models. Therefore, the use of photogrammetric techniques can improve efficiency and accuracy in orthodontic treatment. Photogrammetry requires several stages and the necessary equipment to produce good results. Photogrammetry itself has advantages and disadvantages. The three-dimensional digital study model is a better alternative to the traditional study model because it is not susceptible to physical damage, requires small digital storage space, can be transmitted instantly electronically, is a means of educating patients, and can be manipulated virtually.